Tingkat Penggunaan Media Massa dan Peran Komunikasi Anggota Kelompok Peternak dalam Jaringan Komunikasi Penyuluhan Sapi Potong - A Saleh (Faculty of Animal Science, Bogor Agricultural University, 2006)
The aims of study were to investigate the communication behavior changes, in term of the level of mass media used by the cattle farmers in utilizing the cattle extension program; and to analyze the participation level of cattle farmers based on their communication roles in the cattle communication network. This research was designed as correlation descriptive survey towards sample of cattle farmers head of families integrated into two groups of advanced category cattle farmers group and two groups of less advanced, lived and having its place of business in three regencies namely the West Java Sukabumi Regency, Central Java Sukohardjo Regency and D.I. Yogyakarta Gunung Kidul Regency. The determination of the regencies and the selected groups were conducted purposively, based on the advance level data of the cattle farmer group derived from the Cattle Farmer Directorate General office of the Ministry of Agriculture. The data analyses were conducted using descriptive analysis comprising of frequency, boxplot, percentage, cross tabulation, correlations matrix, inferences about a mean factor or T2 Hotelling, and byplot test. The results of research showed: (1) there was significant difference among the communication behavior in advanced cattle farmers group and the less advanced group, indicating (the circumstance) a level of mass media usage by cattle farmers in getting information. From prioritized the interpersonal communication relationship in receiving and diffusing information to the media communication behavior, particularly in behavior impact of television broadcast and newspapers. (2) The level of cattle farmers communication role in a cattle communication network comprising of star, mutual pairs and neglectee, did not indicate a communication role as isolate. The advanced cattle farmers group members had a dominant communication role as neglectee, while the less advanced group had a dominant role of mutual pairs. The role of the star, was found more in the less advanced group compared with the advanced group. Key words: cattle extension, communication behavior, communication network, mass media usage, role of group members